Student's Readiness in Using Virtual Reality for Physics Learning - Rahmat Rizal; Irwan Muhammad Ridwan; Herni Yuniarti Suhendi; Ifa Rifatul Mahmudah (Journal of Teaching and Learning)
Virtual Reality (VR) technology in learning activities assists in visualizing abstract phenomena of physics concepts. This technology supports the delivery of effective and meaningful learning experiences. The main objectives of this study, therefore, are to analyze the level of students' readiness to use VR technology in higher education, and to analyze the factors most affecting students' readiness to use VR technology in physics learning. The research employed a questionnaire-survey method with 127 physics education students from a university in Indonesia, distributed based on age, gender, study level, geographical background, and family economic status. Data collection uses a Likert-scale questionnaire containing ten factors of student readiness for using VR. Data analysis techniques included percentages, the Pearson Product Moment Correlation, and multiple regression. The results of this study indicate that the level of students' readiness to use VR technology falls into the intermediate category (71%). The two factors most influencing students' readiness, that were identified from the correlation coefficients, are the availability of access to VR devices and basic technical skills in operating VR technology. Students' readiness to use technology in learning serves as the basis for determining which steps should be prioritized to prepare for technology-enhanced learning, ensuring that the technology positively impacts the learning quality.